Optimization of L-Asparaginase production by Bacillus subtilis - Castro, Daniel Figueiredo de (2022)
Currently the enzyme L-Asparaginase (L-ASNase) is used in both food and pharmaceutical industries due to its ability to catalyze the hydrolysis reaction of the amino acid L-Asparagine in ammonia and aspartic acid. In the food industry, this enzyme is used in a way to prevent the formation of cancerous compounds in foods, such as acrylamide. In the pharmaceutical industry, L-ASNase is used in the treatment of acute lymphoblastic leukemia (ALL) once it prevents cancer cells from growing as a result of the decrease in exogenous L-Asparagine. As cancer cells have low levels of the enzyme asparagine synthase, they are dependent on the absorption of this amino acid from the physiological environment to survive. Thus, the optimized production of L-ASNase, particularly with high purity, is highly desired, particularly for medical applications. In the production of this enzyme, several microorganisms are used, such being the most commonly used Escherichia coli and Erwinia sp. However, associated with these bacteria are the L-ASNase production with low yields and side effects, which leads to increased demand for other sources of production. This way, Bacillus subtilis appears as an alternative microorganism for the production of this therapeutic enzyme. This organism has been studied for several decades, being the prokaryote most understood in terms of molecular and cellular biology, playing an important role as a model for gram-positive bacteria research. On this work, several factors of the fermentation process were optimized such as inductor’s concentration (0.5, 1, 2, 3 and 5% (v/v) of xylose), temperature after induction (25, 30, 35 and 40ºC) and incubation times (8, 12, 18, 24 and 36h). In the optimum fermentation conditions (3% of xylose, 30ºC during 24h) it was obtained a L-ASNase, after cellular lysis, with an enzymatic activity of 0,756 U/mL, a specific activity of 0,107 U/mg and a purity of 21,97 %.